2021
DOI: 10.1021/acsbiomaterials.1c00217
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Exosomes as Diagnostic Biomarkers and in Targeted Drug Delivery: Progress in Clinical and Preclinical Applications

Abstract: Exosomes are cell-derived vesicles containing heterogeneous active biomolecules such as proteins, lipids, mRNAs, receptors, immune regulatory molecules, and nucleic acids. They typically range in size from 30 to 150 nm in diameter. An exosome’s surfaces can be bioengineered with antibodies, fluorescent dye, peptides, and tailored for small molecule and large active biologics. Exosomes have enormous potential as a drug delivery vehicle due to enhanced biocompatibility, excellent payload capability, and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 422 publications
(825 reference statements)
0
109
0
Order By: Relevance
“…Simple incubation with surfactants like saponin or triton can increase the membrane permeability of exosomes and facilitate cargo loading, among which saponin is the most widely used surfactant in this field (Huda et al, 2021). As a natural surfactant, saponin interacts with the membrane-bound cholesterol, which creates pores and increases the permeability of cell/exosome membranes (Jamur and Oliver, 2010).…”
Section: Saponin-assisted Permeationmentioning
confidence: 99%
“…Simple incubation with surfactants like saponin or triton can increase the membrane permeability of exosomes and facilitate cargo loading, among which saponin is the most widely used surfactant in this field (Huda et al, 2021). As a natural surfactant, saponin interacts with the membrane-bound cholesterol, which creates pores and increases the permeability of cell/exosome membranes (Jamur and Oliver, 2010).…”
Section: Saponin-assisted Permeationmentioning
confidence: 99%
“…Until January 2021, there were 205 clinical trials related to exosome research. Of the 205 trials, around 87 trials involved cancer-related studies (179). Among these clinical trials, exosomebased phase I and II clinical trials have been completed in advanced lung cancer patients showing promising data (148).…”
Section: Patents Of Exosomes In Cancer Therapymentioning
confidence: 99%
“…Studies have shown that exosomes from endothelial cells interact with the BBB, whereas exosomes from cultured GBM cells could not. However, hypoxic GBM cells produced exosomes capable of modulating BBB permeability [127]. Cancer cells also produce exosomes which weaken the BBB, which may be a way to pre-condition the brain for metastasis [128].…”
Section: Evs As Vehicles For Brain Tumor Deliverymentioning
confidence: 99%
“…Since some exosomes can cross the BBB, they may be used as delivery vehicles for conventional chemotherapeutic drugs. Drugs may be loaded into exosomes by a variety of methods including simple incubation and passive uptake, sonication, electroporation, freeze-thaw or use of surfactants [127]. A study by Yang and colleagues showed that bEND.3-derived exosomes could be loaded with doxorubicin and paclitaxel (7.3 ng and 132.9 ng of drug per 1 µg exosome) and showed better therapeutic efficacy than free drug in a zebrafish tumor model [131].…”
Section: Evs As Vehicles For Brain Tumor Deliverymentioning
confidence: 99%